Entrepreneurship In Rural Areas in Poland – Disparities, Main Determinants and Perspectives - Patrycja BRAŃKA (Communications of International Proceedings, 2024)
Entrepreneurship is one of the main factors determining the multifunctional development of rural areas - a concept that has been pushed for over twenty years by EU and national policies in relation to areas where agriculture cannot be the main source of income for  the residents. Recognizing the factors determining the level of entrepreneurship development in rural areas as well as the rate of changes is of key importance in understanding its disparities throughout the country and individual regions. The aim of the article is to identify the level of entrepreneurship development in rural areas in Poland, its spatial differentiation, as well as its directions and main factors. As part of the conducted research, the level of entrepreneurship in rural areas in Poland has been analyzed using a synthetic development indicator. The period 2013 and 2024 were taken into consideration. The analysis was carried out for the smallest units of territorial administration in the country - communes. Rural and urban-rural communes were taken into account. This allowed to formulate conclusions regarding the differentiation of the level of entrepreneurship development in rural areas, as well as its changes in the last 10 years. Additionally, analyzes have been carried out on the spatial diversity of industries such as agricultural processing, tourism and non-agricultural activities. The main conclusions that were formulated concern significant disparities in the level of entrepreneurship development in rural areas in Poland both in regional and local systems. Most of the disparities result from historical factors as well as they are related to local conditions. Historical conditions are particularly visible in the differences between the level of entrepreneurship in the eastern and western parts of the country (east and west of the Vistula). The effects of the partition period (when in the years 1795-1918 Poland was not a sovereign country) are still visible – primarily in the lower quality of technical, road and railway infrastructure in the eastern provinces of Poland.
Keywords: rural areas; rural entrepreneurship; rural development; conditions for the development of rural entrepreneurship in Poland